United Nations Demographic Yearbook 2021 - United Nations Department of Economic; Social Affairs (United Nations, 2022)
The Demographic Yearbook 2021 is the seventy-second issue in a series published by the United Nations since 1948. It contains tables on a wide range of demographic statistics, including a world summary of selected demographic statistics, statistics on the size, distribution and trends in national populations, fertility, fetal mortality, infant and maternal mortality, general mortality, nuptiality and divorce. Data are shown by urban/rural residence, as available. The volume provides Technical Notes, a synoptic table, a historical index and a listing of the issues of the Demographic Yearbook published to date. This issue of Demographic Yearbook contains data as available including reference year 2021.